ANALYSIS THE IMPACT OF COPING STRESS ON THE LEARNING OUTCOMES SENIOR HIGH SCHOOL GRADE STUDENTS - Faqih Purnomosidi; Anisa Indriyani; Bowo Wijianto (EDU RESEARCH, 2024)
Being at the level of class XII students is very special for everyone, special because they will face graduation exams and choose a career for the next level of education. Quite a few of them need strategies for managing their stress, because even though they are in the late teenage stage, they still need guidance. Stress coping is how someone has a strategy for dealing with stress. This research aims to determine coping stress in class XII high school students. The informants for this research were seven people who were class XII students. The method used is qualitative with interviews. The results of this research show that the seven informants have good stress coping as class XII high school students.